2023
DOI: 10.1186/s12967-023-04110-w
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cancer remission after COVID-19: insights from the pandemic and their relevance for cancer treatment

Abstract: Early in the COVID-19 pandemic, it emerged that the risk of severe outcomes was greater in patients with co-morbidities, including cancer. The huge effort undertaken to fight the pandemic, affects the management of cancer care, influencing their outcome. Despite the high fatality rate of COVID-19 disease in cancer patients, rare cases of temporary or prolonged clinical remission from cancers after SARS-CoV-2 infection have been reported. We have reviewed sixteen case reports of COVID-19 disease with spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Spontaneous tumor reduction after SARS-CoV-2 infection is rare. Generally, patients with cancer, as a immunocompromised group, showed a higher mortality rate when infected ( 7 ). However, recent reports have demonstrated that the imaging and serological symptoms of certain cancer patients were relieved after SARS-CoV-2 infection ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous tumor reduction after SARS-CoV-2 infection is rare. Generally, patients with cancer, as a immunocompromised group, showed a higher mortality rate when infected ( 7 ). However, recent reports have demonstrated that the imaging and serological symptoms of certain cancer patients were relieved after SARS-CoV-2 infection ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report indicated that SARS-CoV-2 is not entirely harmful, and that it can also bring some benefits with unknown mechanisms ( 6 ). A number of patients with malignancies experienced tumor reduction or significant remission during SARS-CoV-2 infection, even though their therapeutic regimens were unchanged ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The success of BCG in immunotherapy is attributed to its ability to induce a long-lasting antitumor immune response, which has been a breakthrough in the field. Curiously, in a recent study exploring the intersection of COVID-19 and cancer, researchers found unexpected instances of temporary or prolonged clinical remission from cancer following SARS-CoV-2 infection, despite the generally severe outcomes of COVID-19 in cancer patients ( 32 ). Sixteen case reports were examined, most of which involved remission after viral infections, with a few cases following anti-SARS-CoV-2 vaccination.…”
Section: Tracing the Links: Exploring Individual Connections In The C...mentioning
confidence: 99%
“…Over the last 3 years, a limited number of cases describing the antitumor effect of SARS-CoV-2 have been reported in the literature, with only a small part of these involving patients who did not receive any antineoplastic treatment. Reported cases included patients diagnosed with lymphoma, multiple myeloma, chronic lymphocytic leukemia, renal cell carcinoma, and colorectal carcinoma, with most of the cases related to hematologic neoplasms, suggesting higher spontaneous remission rates for these malignancies 2,5–10 . Extended patient follow-up and research are required to fully understand the molecular mechanisms, confirm the relationship between COVID-19 disease and cancer, and determine the clinical implications of these interactions 5 …”
mentioning
confidence: 99%